O Radix Jesse - Green, Susan L. (Susan Lesley), author.
1 online resource
Keywords: This book is the first detailed investigation to focus on the late medieval use of Tree of Jesse imagery, traditionally a representation of the genealogical tree of Christ. In northern Europe, from the mid-fifteenth to the early sixteenth centuries, it could be found across a wide range of media. Yet, as this book vividly illustrates, it had evolved beyond a simple genealogy into something more complex, which could be modified to satisfy specific religious requirements. It was also able to function on a more temporal level, reflecting not only a clerical preoccupation with a sense of communal identity, but a more general interest in displaying a family's heritage, continuity and/or social status. It is this dynamic and polyvalent element that makes the subject so fascinating.